2020
DOI: 10.21037/tcr.2020.03.72
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the relationship between Ki-67 expression and chemotherapy and prognosis in advanced non-small cell lung cancer

Abstract: Background To analyse the relationship between the Ki-67 index of advanced non-small cell lung cancer (NSCLC) and the objective response rate (ORR) and progression-free survival (PFS) of patients who received chemotherapy. Methods The Ki-67 index of advanced NSCLC pathology was established by immunohistochemistry; using univariate and multivariate analyses, we retrospectively analysed the relationship between the Ki-67 index of 112 advanced NSCLC patients in our hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Therefore, the results of the present study suggested that segmentectomy should be the preferred surgical procedure for early-stage NSCLC. Some studies have reported that the expression level of Ki-67 and tumor stage affect PFS, which is consistent with the results of this study [ 10 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the results of the present study suggested that segmentectomy should be the preferred surgical procedure for early-stage NSCLC. Some studies have reported that the expression level of Ki-67 and tumor stage affect PFS, which is consistent with the results of this study [ 10 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, this method may increase the incidence of pneumothorax by approximately 15% [ 9 ]. High expression of Ki-67 is an unfavorable factor affecting progression-free survival (PFS) [ 10 ]. Therefore, developing a noninvasive method to accurately predict Ki-67 expression in stage IA LUAD preoperatively is highly important.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically in lung cancer, cells expressing Ki-67 exhibit heightened proliferation, greater invasiveness, and a higher likelihood of lymph node metastasis (22). Its higher expression might also be an indicator of shortened progression-free survival (PFS) time (23). In addition, it yields prognostic importance in lung adenocarcinoma subtypes, suggests its potential as a marker in lung neuroendocrine tumors, and identifies its clinical significance in advanced NSCLC, particularly in predicting chemotherapy efficacy (23, 24).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of predicting e cacy, Ki-67 index might predict the e cacy of chemotherapy. Wang et al 19 reported that the high expression of Ki-67 may also be an indicator of the shortened PFS of chemotherapy. Nevertheless, studies that have used Ki-67 index to predict the e cacy of targeted therapy in advanced NSCLC are rare.…”
Section: Discussionmentioning
confidence: 99%